Gene-environment interaction in functional hypothalamic amenorrhea - Barbagallo, Federica; Bosoni, David; Perone, Valeria; Cucinella, Laura; Dealberti, Davide; Cannarella, Rossella; Calogero, Aldo E.; Nappi, Rossella E. (Frontiers in Endocrinology, 2024)
Functional hypothalamic amenorrhea (FHA) is a common cause of amenorrhea and chronic anovulation in adolescent girls and young women, diagnosed after excluding other organic causes. It is commonly associated with calorie restriction, excessive physical exercise, and psychosocial stress. These stressors alter the pulsatile secretion of gonadotropin-releasing hormone, leading to a chronic condition of hypoestrogenism and significant health consequences. Recent evidence has highlighted a genetic predisposition to FHA that could explain interindividual variability in stress response. Indeed, not all women experience FHA in response to stress. Rare variants in genes associated with idiopathic hypogonadotropic hypogonadism have been identified in women with FHA, suggesting that these mutations may contribute to an increased susceptibility of women to the trigger of stress exposure. FHA appears today as a complex disease resulting from the combination of genetic predisposition, environmental factors, and epigenetic changes. Furthermore, the genetic background of FHA allows for the hypothesis of a male counterpart. Despite the paucity of data, preliminary findings indicate that an equivalent condition of FHA exists in men, warranting further investigation. This narrative review aims to summarize the recent genetic evidence contributing to the pathophysiology of FHA and to raise awareness on a possible male counterpart.